CLEAN WATER, HEALTHY LIVES: INVESTIGATING THE IMPACTS OF UNSAFE DRINKING WATER ON HUMAN’S HEALTH IN KOTTLI SATTIAN - Haleema Sadia; Dr. Abid Ghafoor Chaudhry (International Journal of Contemporary Issues in Social Sciences, 2024)
This study investigates the impacts of unsafe drinking water on human health in the villages of Balawara and Gali Par in Kottli Sattian, a Tehsil in Pakistan’s Rawalpindi District. Through interviews, surveys, and focus group discussions, this exploratory research reveals alarming levels of water contamination and a high prevalence of waterborne diseases such as diarrhea, hepatitis, and malaria. Approximately 90% of residents rely on unprotected open wells, which are prone to contamination by bacteria, insects, and animal waste. The lack of proper sanitation facilities exacerbates this issue, and community awareness about safe drinking water practices is extremely low. The inadequate infrastructure is highlighted by the presence of only one non-functional filtration plant in the entire Tehsil. Additionally, some residents use bore water, which is often discolored and malodorous, and face severe water shortages during the summer months. The study concludes that addressing this public health crisis requires a multi-faceted approach, including the construction of protected wells and functional water filtration plants, improved sanitation facilities, community education campaigns, and increased involvement of governmental and non-governmental organizations to provide the necessary resources and support for water and sanitation projects.